Network meta-analysis of efficacy and safety of drugs for the treatment of moderate to severe ulcerative colitis - Zhang, Wenkai; Zhao, Songbo; Li, Jipin; Sun, Yihua; Wang, Xiang (Frontiers in Pharmacology, 2025)
PurposeTo guide the drug selection for treatment of moderate to severe ulcerative colitis (UC) by evaluating the efficacy and safety of various drugs.MethodsThis systematic review searched the Embase, PubMed, The Cochrane Library, and Web of Science databases and included randomized controlled trials (RCTs) based on the drugs used alone or in combination for treating UC. Moreover, the Stata17.0 software was employed for statistical analysis and results were reported as relative risk (RR) and 95% confidence interval (CI).ResultsFor the efficacy of induction, upadacitinib ranked first in clinical response, clinical remission, and endoscopic improvement rates, with cumulative probabilities of 96.0%, 99.3%, and 99.0%, respectively. Moreover, for the efficacy of maintenance, upadacitinib ranked first in both clinical remission and endoscopic improvement with a cumulative probability of 93.2% and 93.3%, respectively. For safety, vedolizumab showed the best incidence of adverse events (AE) with 16.8% cumulative probability, while upadacitinib showed the best incidence of serious adverse events (SAE) with 13.8% cumulative probability.ConclusionIn a systematic review and network meta-analysis, we found upadacitinib showed the best efficacy and safety in to be ranked highest in patients with moderate to severe ulcerative colitis. More trials of direct comparisons are needed to inform clinical decision making with greater confidence.